2015
DOI: 10.1073/pnas.1417856112
|View full text |Cite
|
Sign up to set email alerts
|

Conserved role of Sonic Hedgehog in tonotopic organization of the avian basilar papilla and mammalian cochlea

Abstract: Sound frequency discrimination begins at the organ of Corti in mammals and the basilar papilla in birds. Both of these hearing organs are tonotopically organized such that sensory hair cells at the basal (proximal) end respond to high frequency sound, whereas their counterparts at the apex (distal) respond to low frequencies. Sonic hedgehog (Shh) secreted by the developing notochord and floor plate is required for cochlear formation in both species. In mice, the apical region of the developing cochlea, closer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
93
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(95 citation statements)
references
References 36 publications
2
93
0
Order By: Relevance
“…This, in turn, leads to the premature differentiation of hair cells. Most recently, the longitudinal expression of the Inhba (Activin A subunit inhibin bA) and Fst (Follistatin) genes were found to be influenced by Shh regulation . It was found that a counter‐gradient activity of Activin A and Fst regulates both hair cell differentiation and cell cycle exit along the longitudinal axis .…”
Section: Shh Signaling To the Cochlear Anlagenmentioning
confidence: 99%
See 1 more Smart Citation
“…This, in turn, leads to the premature differentiation of hair cells. Most recently, the longitudinal expression of the Inhba (Activin A subunit inhibin bA) and Fst (Follistatin) genes were found to be influenced by Shh regulation . It was found that a counter‐gradient activity of Activin A and Fst regulates both hair cell differentiation and cell cycle exit along the longitudinal axis .…”
Section: Shh Signaling To the Cochlear Anlagenmentioning
confidence: 99%
“…Most recently, the longitudinal expression of the Inhba (Activin A subunit inhibin bA) and Fst (Follistatin) genes were found to be influenced by Shh regulation. 106 It was found that a countergradient activity of Activin A and Fst regulates both hair cell differentiation and cell cycle exit along the longitudinal axis. 107 Even though the Shh pathway was primarily associated with timing of differentiation along the longitudinal axis, we included it because it is an important morphogen and it is critical for regulating the timing of cochlear development.…”
Section: Shh Signaling To the Cochlear Anlagenmentioning
confidence: 99%
“…Auditory sensory progenitors (pro-sensory cells) exit the cell cycle in an apical-to-basal gradient 48 (Ruben, 1967;Chen and Segil, 1999;Lee et al, 2006), whereas their differentiation into hair 49 cells and supporting cells occurs in an opposing, basal-to-apical gradient (Chen et al, 2002). 50 4 gradient within the differentiating auditory sensory epithelium (Son et al, 2015). Activins, which 78 belong to the transforming growth factor (TGF)-β superfamily of cytokines, control a broad range 79 of biological processes, including reproduction, embryonic axial specification, organogenesis 80 and adult tissue homeostasis (reviewed in (Namwanje and Brown, 2016)).…”
Section: Introduction 41mentioning
confidence: 99%
“…3 The inner ear SE typically contains mechanosensitive receptors, the hair cells (HCs) and neighboring supporting cells (SCs); however, the HCs and SCs in each individual present unique morphological and geneexpression profiles. [8][9][10] Moreover, the distinct developmental properties of the HCs and SCs at each cochlear turn contribute to the tonotopic axis. The mammalian cochlea harbors two types of HCs, outer HCs (OHCs) and inner HCs (IHCs), which are, respectively, sound amplifiers and primary sensory cells.…”
mentioning
confidence: 99%
“…Recent studies suggest that Shh, retinoic acid, and Bmp7 contribute to tonotopic axis formation, and their dysregulation leads to defective frequency distribution. [8][9][10] Moreover, the distinct developmental properties of the HCs and SCs at each cochlear turn contribute to the tonotopic axis.…”
mentioning
confidence: 99%